Urban climate research in Warsaw: the results of microclimatic network measurements - Kuchcik, Magdalena; Błażejczyk, Krzysztof; Milewski, Paweł; Szmyd, Jakub (IGiPZ PAN, 2014)
The paper presents some aspects of Warsaw’s climate, in particular the urban heat island. UHI changes in different seasons and in different air mass types were analysed over the years 2011-2012. Average UHI in Warsaw is of a diamond shape which reflects the distribution of the densest built area and exceeds 2.0°C in the city centre compared to the airport station. In subtropical air mass, the intensity of UHI on the left side of the Vistula River reached 7.7°C. The basis for the analysis is the microclimatic measurement network of 28 permanent points in Warsaw and its surroundings, operated by IGSO PAS and completed by data from 7 other stations. This dense network became the IGSO PAS’ input into an UHI project titled ‘Development and application of mitigation and adaptation strategies and measures for counteracting the global Urban Heat Islands phenomenon (UHI)’ implemented through the Central Europe Program and co-financed by the ERDF.
24 cm
Keywords: city climate; network of microclimatic measurements; urban heat island; Warsaw